Job crafting as dynamic displays of gender identities and meanings in male‐dominated occupations. Issue 2 (22nd December 2020) - Yu, Ai; Jyawali, Harishchandra
Abstract: In this article, we explore how women craft their jobs in male‐dominated occupations in ways that respond to the job demands relating to contradictory gender expectations. With material from 21 interviews with female chefs working in professional kitchens, we show, through the lens of constructing gender identities and meanings at the gender‐body nexus, that three job crafting practices—negotiating physical competence, reframing creativity, and managing men co‐workers reactions—are invented as creative responses to gender‐related job demands. The findings contribute to the job crafting literature by showing that women's job crafting in male‐dominated occupations is less about increasing or decreasing certain types of job demands, but more about enacting "dynamic displays"— material, discursive, and fluid —of their gender identities and meanings as situated responses to a given job demand being made. Our research indicates the importance of understanding the conditions under which job crafting is mostly likely to generate positive, negative, or mixed experiences over time.